A Four-year Observational Study of Exercise Tolerance Test for Evaluation of Patients with Chest Pain in A Tertiary Care Hospital of Bangladesh (Bangladesh Critical Care Journal, 2026)
Background: Cardiovascular disease is a major cause of death worldwide. Ischemic Heart Disease (IHD) is preventable and reversible if early screening and elimination of the risk factors like life style modification and dietary intervention can be done. Stress electrocardiography or treadmill stress testing is a well validated noninvasive diagnostic modality available to clinicians at low cost yet providing valuable functional data for coronary artery disease (CAD) diagnostic and prognostic evaluation. Aim of the study: to know the incidence of positive test suggesting myocardial ischemia among the patient evaluated for chest pain. The demographic and clinical factors associated with those subjects and assessment of exercise capacity of the study group for planning future management. Methods: This is a retrospective observational study was carried out in the department of Cardiology BIRDEM General Hospital Dhaka, Bangladesh from 2021 to 2024. Total 1312 patients who were attend to the institute between 2021 to 2024 was studied and evaluated the patient suspected to have CAD with their functional capacities by doing ETT from inpatient and also from outdoors. Documents were evaluated for Gender, Age, Glycemic Status, Blood Pressure, Dyslipidemia, Body Mass Index (BMI) and the impression of ETT (Positive, Normal, Equivocal, Submaximal and Inconclusive). Results: Among total 1312 patients, 60.1% were male and 39.9% were female. Majority of them were Diabetic and Hypertensive. ETT was found positive among 953 (72.63%) patients with slightly male predominance. Most of the patient having Positive ETT belongs to age 45-57 years. Different types of risk factors were assessed and found in higher incidence among ETT positive study population like 86.51% were over 50 years age group, 79.50% were male, 90.11% of the Diabetes, 86.33% of the Hypertensive. 84.08% had Dyslipidemia and 57.57% of population of had increased BMI. The incidence of positive stress test was proportionately higher in subjects who had greater numbers of comorbidities than those with lesser comorbidities in this study. Functional capacity was assessed by calculating METS during doing ETT revealed 65.5% had above average, 29.5% had average and remainder had below average exercise capacity. Conclusion: Electrocardiographic stress test is a valuable inexpensive non-invasive screening test in patients with multiple risk factors of CAD presented with chest discomfort. It can also be used to assess the functional capacity which will guide further therapeutic measure.Bangladesh Crit Care J March 2026; 14 (1): 34-38